Regret theory: A new foundation - Diecidue, Enrico; Somasundaram, Jeeva (Elsevier, 2017)
We present a new behavioral foundation for regret theory. The central axiom of this foundation — trade-off consistency — renders regret theory observable at the individual level and makes our foundation consistent with a recently introduced empirical and quantitative measurement method. Our behavioral foundation allows deriving a continuous regret theory representation and separating utility from regret. The axioms in our behavioral foundation clarify that regret theory minimally deviates from expected utility by relaxing transitivity only.
Keywords: Regret theory; Trade-off consistency; Expected utility; Transitivity; 53 Ciencias Económicas::5307 Teoría económica; ODS 4 - Educación de calidad